The representation of object distance: evidence from neuroimaging and neuropsychology - Berryhill, Marian; Olson, Ingrid R. (Frontiers in Human Neuroscience, 2009)
Perceived distance in two-dimensional images relies on monocular distance cues. Here, we examined the representation of perceived object distance using a continuous carry-over adaptation design for fMRI. The task was to look at photographs of objects and make a judgment as to whether or not the item belonged in the kitchen. Importantly, this task was orthogonal to the variable of interest: the object’s perceived distance from the viewer. In Experiment 1, whole brain group analyses identified bilateral clusters in the superior occipital gyrus (approximately area V3/V3A) that showed parametric adaptation to relative changes in perceived distance. In Experiment 2, retinotopic analyses confirmed that area V3A/B reflected the greatest magnitude of response to monocular changes in perceived distance. In Experiment 3, we report that the functional activations overlap with the occipito-parietal lesions in a patient with impaired distance perception, showing that the same regions monitor implied (two-dimensional) and actual (three-dimensional) distance. These data suggest that distance information is automatically processed even when it is task-irrelevant and that this process relies on superior occipital areas in and around area V3A.